2010
DOI: 10.2337/db09-1698
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Replication Is Increased in Donor Organs From Young Patients After Prolonged Life Support

Abstract: OBJECTIVEThis study assesses β-cell replication in human donor organs and examines possible influences of the preterminal clinical conditions.RESEARCH DESIGN AND METHODSβ-Cell replication was quantified in a consecutive series of n = 363 human organ donors using double immunohistochemistry for Ki67 and insulin. Uni- and multivariate analysis was used to correlate replication levels to clinical donor characteristics and histopathologic findings.RESULTSβ-Cell replication was virtually absent in most donors, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 21 publications
7
56
0
Order By: Relevance
“…In the adult pancreas, human β cell proliferation is extremely low (5,31). It was found that human β cell replication could be activated not only upon glucose stimulation (32), but also by adenovirus-mediated overexpression of cell-cycle regulators (33).…”
Section: Figurementioning
confidence: 99%
“…In the adult pancreas, human β cell proliferation is extremely low (5,31). It was found that human β cell replication could be activated not only upon glucose stimulation (32), but also by adenovirus-mediated overexpression of cell-cycle regulators (33).…”
Section: Figurementioning
confidence: 99%
“…These thresholds range from two to 15 CD3 + or CD45 + cells adjacent to or infiltrating the islet [6,[9][10][11][12][13][14]. However, recent observations in a cohort of 363 non-diabetic donor pancreases indicate that the level of background infiltration in the pancreatic parenchyma is highly variable and dependent on the clinical conditions surrounding organ retrieval, with the highest levels of infiltration observed in patients with a prolonged duration of life support [15]. Therefore, it was generally agreed that the threshold level should be substantially higher than the highest levels found in published controls; a level of 15 CD45 + cells (approximately twice the highest number of CD45 + cells found in a single islet in a cohort of 62 control donor pancreases [14]) was accepted as a suitable threshold (Fig.…”
Section: Consensus Definition Of Insulitismentioning
confidence: 99%
“…Although islet-autoreactive CD8 + T cells were detected [3], the level of insulitis remains surprisingly mild, even in patients with recent-onset type 1 diabetes and death due to ketoacidosis [4]. This picture is complicated by background infiltration in the exocrine pancreas, partly due to peri-mortem changes, with the highest levels of infiltration observed in young patients after prolonged life support [5]. Even independently of postmortem changes, type 1 diabetes affects the exocrine as well as the endocrine pancreas [6]; this raises the question whether the limited infiltration of leucocytes is specifically targeted to pancreatic beta cells.…”
mentioning
confidence: 99%